Meat quality evaluation of breast fillets of different strains of chicken broilers with deep pectoral myopathy - Giampietro-Ganeco, Aline; de Barba, Bruna Regina; Galvão, Alessandro Cazonatto; Trindade, Marco Antonio; Borba, Hirasilva [UNESP]; Stefani, Lenita Moura; Boiago, Marcel Manente; da Silva Robazza, Weber (Oxford University Press (OUP), 2024)
Chicken meat is a significant source of protein and other nutrients. The poultry industry is responsible for creating many jobs and is essential to the global economy. Thus, the sector demands high-quality products to satisfy consumers' expectations. Advances in poultry production with the rapid creation of heavier birds have increased the incidence of deep pectoral myopathy, provoking substantial losses to the sector. Several quality indicators of breast fillets obtained from chicken broilers of the strains Cobb 500 and Ross AP95 were measured to evaluate the strain influence on the characteristics of broilers' breast fillets with different severities of deep pectoral myopathy (DPM). Overall, the myopathy affected the quality attributes of the breast fillets more significantly than the broilers strain. However, the results of some individual quality attributes are strain-specific. Moreover, myopathy severity tends to soften the differences between the characteristics of the strains.
Keywords: Breast fillets; chicken meat; Cobb 500; hierarchical clustering; meat quality; myopathy severity; Ross AP95